Romeo and Juliet - Shakespeare, William, 1564-1616.; Gibson, Rex. (Cambridge, U.K. ; New York : Cambridge University Press, 1998)
Contains the complete script to Shakespeare's "Romeo and Juliet" and includes a running synopsis of the action, explanations of unfamiliar words, and activities designed to help students better understand the play.
Young Adult.
Young Adult
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Vendetta -- Italy -- Verona -- Drama; Young adult drama, English; Youth -- Italy -- Verona -- Drama; English drama -- History and criticism; Tragedies; Vendetta -- Drama; Verona (Italy) -- Drama; Tragedies